2008
DOI: 10.1074/jbc.m701803200
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for HSP90 in Cancer Cell Invasion Involves Interaction with the Extracellular Domain of HER-2

Abstract: HSP90 is a ubiquitously expressed molecular chaperone that controls the folding, assembly, intracellular disposition, and proteolytic turnover of many proteins, most of which are involved in signal transduction processes. Recently, a surface form of HSP90 has been identified and associated with cell migration events. In this paper, we explore the interaction of surface HSP90 with HER-2, a receptor-like glycoprotein and member of the ErbB family of receptor tyrosine kinases that play central roles in cellular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
167
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(180 citation statements)
references
References 60 publications
11
167
1
1
Order By: Relevance
“…Taking into account the documented metastatic potential of BCSC 37 this result is in line with previously reported data relating eHSP90 with invasion and metastasis. 24,26,27 These observations suggest that eHSP90 could be considered as a potential CSC marker in the case of breast cancer.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Taking into account the documented metastatic potential of BCSC 37 this result is in line with previously reported data relating eHSP90 with invasion and metastasis. 24,26,27 These observations suggest that eHSP90 could be considered as a potential CSC marker in the case of breast cancer.…”
Section: Discussionmentioning
confidence: 94%
“…36 Moreover in the same work we have reported that mAb4C5 disrupts the formation and/or stabilization of the eHSP90/eCdc37/EGFR complex thus leading to inhibition of the invasive capacity of the MDA-MB-231 cells. Taking into account all the above, it is tempting to speculate that eHSP90, by acting as an extracellular chaperone, is crucial not only for the invasive potential of breast cancer cells 24,27 but also for the maintenance of stem cell properties such as self-renewal capacity and tumorigenic ability that are necessary for primary tumor growth. Finally our results further support and reinforce the anti-cancer potential of mAb 4C5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Webb et al [34] showed that geldanamycin (GA) down regulates MET expression at nanamolar concentrations, thus inhibiting HGF/SF-mediated cell motility and invasion. Another Hsp90 client protein, HER2 has been proposed to interact extracellularly with Hsp90 -activating HER2 by heterodimerisation with HER3, leading to actin remodelling and cell motility via activation of signal transduction pathways MAPK and PI3 K-Akt [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Through an interaction with the extracellular domain of Neu/Her-2, surface HSP90 is involved in heregulin-induced Neu/Her-2 activation and signaling, leading to cytoskeletal rearrangements and migration and invasion of breast cancer cells (7). Recent studies have shown that HSP90 could be secreted by keratinocytes, nonsmall cell lung cancer CL1-5 cells, and breast cancer MCF-7 cells (8 -12).…”
mentioning
confidence: 99%